Outcome of Tumor Resection by Endoscopic Binarial Trans-Sphenoidal Approach in Pituitary Adenoma Patients (Medical Forum Monthly, 2020)
Objective: To determine the frequency of complete tumor resection by endoscopic binarial trans-sphenoidal approach in pituitary adenoma patients presenting to a tertiary care hospital.Study design: Descriptive case seriesPlace and Duration of Study: This study was conducted at the Department of Neurosurgery Punjab Institute of Neurosciences Lahore from July 2017 to December 2017.Materials and Methods: Sixty patients with pituitary adenoma and either gender, age 25 to 60 years and diagnosis of pituitary adenoma by magnetic resonance imaging during last one year were included. Patients having previous surgery or intervention for any pituitary problems determined by history, diabetic patients determined by history and random blood sugar and any history of connective tissue disorders e.g. rheumatoid arthritis and SLE were excluded. Patients were followed for 6 week to determine the outcome i.e. no residual tumor left as determined by magnetic resonance imaging. Nasal trumpet maybe placed overnight. All patients were treated according to department protocols under general anesthesia and patients were followed for 6 week to determine the outcome i.e. no residual tumor left as determined by magnetic resonance imaging. Adenoma size was treated as effect modifier and data was stratified subsequently.Results: The mean age was 50.02±8.2 years. Forty three (71.7%) patients were male and 17 (28.3%) females. Fifty six patients (93.3%) showed complete resection on MRI using endoscopic binarial trans-sphenoidal approach. There was no effect of age and gender of patient on outcome in sampled population. Tumor size significantly affected the outcome i.e. complete resection.Conclusion: Endoscopic binarial trans-sphenoidal approach for resection of pituitary adenoma is excellent at current sample size. As in our study, 93.3% patients showed complete resection. There was no effect of age and gender of patient on outcome in sampled population.